Influence of Daily K-pop Watching Duration and Expenditure on K-pop Merchandise on Intention to Purchase Concert Tickets: Moderating Effect of Likeability Level - Wily Mohammad; Hanif Saifurrahman (Tinta Emas Publisher, 2023)
This quantitative study delves into the intricate landscape of K-pop fandom within the United States, particularly focusing on the influences that shape intentions to purchase concert tickets among individuals aged 15-29. With a carefully selected sample of 98 participants from a population of 65.47 million, this research employs the Structural Equation Model-Partial Least Squares (SEM-PLS) method to analyze secondary data sourced from a figshare dataset by Rraman (2020). The study's findings shed light on the diverse connections between K-pop-related factors and concert attendance intentions. Specifically, while